2013
DOI: 10.1016/j.elspec.2012.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Between photocatalysis and photosynthesis: Synchrotron spectroscopy methods on molecules and materials for solar hydrogen generation

Abstract: Energy research is to a large extent materials research, encompassing the physics and chemistry of materials, including their synthesis, processing towards components and design towards architectures, allowing for their functionality as energy devices, extending towards their operation parameters and environment, including also their degradation, limited life, ultimate failure and potential recycling. In all these stages, xray and electron spectroscopy are helpful methods for analysis, characterization and dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
3
14
0
Order By: Relevance
“…Figure 1 shows the in situ spectro-electrochemical cell [17]. At the oxygen x-ray absorption pre-edge at around 525 eV we notice the spectral intensity which was previously assigned to two different electron hole transitions into the charge transfer band and upper Hubbard band [18,19]. These are likely the two different electron holes which had been hypothesized by Kennedy and Frese in 1978 [7].…”
Section: Resultsmentioning
confidence: 73%
“…Figure 1 shows the in situ spectro-electrochemical cell [17]. At the oxygen x-ray absorption pre-edge at around 525 eV we notice the spectral intensity which was previously assigned to two different electron hole transitions into the charge transfer band and upper Hubbard band [18,19]. These are likely the two different electron holes which had been hypothesized by Kennedy and Frese in 1978 [7].…”
Section: Resultsmentioning
confidence: 73%
“…The shaded area peaks between 525 and 527 eV, as obtained by deconvolution and least square fitting of the spectrum, have been associated with transitions into the charge transfer band (CTB) and upper Hubbard band (UHB) [65]. It turns out that the higher energy hole state can be associated with a capacitive surface defect state as determined from impedance spectroscopy [66,67]. Closer investigation of the green "in situ"spectrum in Fig.…”
Section: Characterization Of Metal Oxidesmentioning
confidence: 97%
“…Although the specific cause of improvement by Si doping has not been unambiguously determined, it is found that incorporation of silicon leads to disorder in hematite structure 14 and results in high carrier density and increased hole mobility after doping. 15 On such Si-doped hematite, it was even possible to detect several different photogenerated hole states with x-ray absorption spectroscopy 16,17 which virtually matched similar hole states that had been determined with impedance spectroscopy. [17][18][19] A renewable and sustainable energy economy will largely require systems, components, and materials, which are based on low-cost and environmental benign precursors and processes that can be scaled up with ease.…”
Section: Introductionmentioning
confidence: 71%
“…15 On such Si-doped hematite, it was even possible to detect several different photogenerated hole states with x-ray absorption spectroscopy 16,17 which virtually matched similar hole states that had been determined with impedance spectroscopy. [17][18][19] A renewable and sustainable energy economy will largely require systems, components, and materials, which are based on low-cost and environmental benign precursors and processes that can be scaled up with ease. Recently, Hamd et al 20 prepared mesoporous a-Fe 2 O 3 thin film with a low-cost sol gel method.…”
Section: Introductionmentioning
confidence: 71%